Harm reduction principles for healthcare settings - Mary Hawk; Robert W. S. Coulter; James E. Egan; Stuart Fisk; M. Reuel Friedman; Monique Tula; Suzanne Kinsky (BMC, 2017)
Abstract Background Harm reduction refers to interventions aimed at reducing the negative effects of health behaviors without necessarily extinguishing the problematic health behaviors completely. The vast majority of the harm reduction literature focuses on the harms of drug use and on specific harm reduction strategies, such as syringe exchange, rather than on the harm reduction philosophy as a whole. Given that a harm reduction approach can address other risk behaviors that often occur alongside drug use and that harm reduction principles have been applied to harms such as sex work, eating disorders, and tobacco use, a natural evolution of the harm reduction philosophy is to extend it to other health risk behaviors and to a broader healthcare audience. Methods Building on the extant literature, we used data from in-depth qualitative interviews with 23 patients and 17 staff members from an HIV clinic in the USA to describe harm reduction principles for use in healthcare settings. Results We defined six principles of harm reduction and generalized them for use in healthcare settings with patients beyond those who use illicit substances. The principles include humanism, pragmatism, individualism, autonomy, incrementalism, and accountability without termination. For each of these principles, we present a definition, a description of how healthcare providers can deliver interventions informed by the principle, and examples of how each principle may be applied in the healthcare setting. Conclusion This paper is one of the firsts to provide a comprehensive set of principles for universal harm reduction as a conceptual approach for healthcare provision. Applying harm reduction principles in healthcare settings may improve clinical care outcomes given that the quality of the provider-patient relationship is known to impact health outcomes and treatment adherence. Harm reduction can be a universal precaution applied to all individuals regardless of their disclosure of negative health behaviors, given that health behaviors are not binary or linear but operate along a continuum based on a variety of individual and social determinants.